Utvärdering av ett lastredessystem för att effektivisera virkeslogistiken vid avlägg - Alm, Tobias (SLU/Dept. of Energy and Technology, 2016)
Today's conventional forestry looks for solutions to bring down handling time of the wood from the forest to the industry. For a timber truck is the handling time depended on the following factors: the actual driving time, crane loading and unloading at the industry. In today's conventional system, much time is spent by the forwarder first to unloading all material at the landing zone and then later for the timber truck to load the same material, both operations requiring crane movement. To bring down this handling time, and create a more rational system, a carrier has been developed which the forwarder can load in the forest and then place loaded at the landing. The timber truck can then back under the carriers and drive away. A machine system using the carrier was modeled and simulated using discrete-event simulation in a program called ExtendSim to study system behavior in different environments. This proposed system was compared with the conventional system and also with a mix of the two. The results from the simulations show a small potential for improvements by introducing the proposed system using a carrier in the forest. The system had some niches where it proved better with regard to total handling time than the conventional system. The proposed system using carriers can give a decreased total handling time, around 7% improvements can be found. On the other hand, the total handling time can also be higher if that system is unbalanced with too much unnecessarily waiting time. This potential occurred when the road distance, from the Industry to the landing, is between 50-100 km. In a comparison with all simulated scenarios the mixed system was the most efficient with regard to the total handling time. The mixed system had overall a lower waiting time than the proposed carrier system. For road distance between 50-200 km the total handling time decreased with 3-6 % compared to the conventional system.